Effectiveness of improving coordination abilities after cardiac surgery: a review - Natalya V. Arkhipova; Svetlana A. Pomeshkina; Evgeniy V. Bykov (Вестник восстановительной медицины)
INTRODUCTION. Bronchopulmonary complications remain the leading cause of postoperative morbidity and prolong the patient’s hospital stay, increasing the cost of treatment.